Research progress on ultrasound medicine in diagnosis and evaluation of chemotherapy effect of breast cancer - Hu, Ningxuan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Breast cancer has the highest incidence rate among cancers in the world and is the main cause of death among female cancer patients around the world. The progress of ultrasound technology has continuously improved the ability to identify the shape and microvessels of breast masses. It plays an important role in the differentiation of benign and malignant breast masses and is the main auxiliary diagnostic method for breast cancer. The widespread implementation of neoadjuvant chemotherapy for breast cancer has improved the survival rate of patients. Evaluating the efficacy after chemotherapy and adjusting chemotherapy strategies as needed can help improve the prognosis of patients. Ultrasound can conduct multi-parameter measurements of breast tumor hardness, blood flow velocity and vascular distribution, which can be applied to evaluate the efficacy of neoadjuvant chemotherapy for breast cancer. This article reviewed the application and research progress of multi-modal ultrasound in the diagnosis and evaluation of chemotherapy efficacy of breast cancer.